2021
DOI: 10.1016/j.psj.2021.101082
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional prevalence of helminth infection in chickens over time: a systematic review and meta-analysis

Abstract: Gastrointestinal helminth parasites are a concern for the poultry industry worldwide as they can affect the health, welfare, and production performance. A systematic review of the prevalence over time in different countries may improve our understanding of gastrointestinal helminthiasis in chickens and subsequently lead to improved poultry health. The aim of this systematic review and meta-analysis was to provide an overview of the published information regarding the epidemiology and the diagnostic approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 52 publications
1
40
0
1
Order By: Relevance
“…The prevalence of gastrointestinal parasite infections varies between regions and countries [ 15 ]. For example, prevalences between 97.6% and 99.2% were reported in Germany [ 16 ], 99.3% in Italy [ 17 ], 72% in Iran [ 18 , 19 ], 73.9% in Thailand [ 20 ], and 95.8% in Zambia [ 21 ], with environmental conditions, age of birds, and availability of intermediate hosts being the main determinants for the variability of parasite prevalence [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of gastrointestinal parasite infections varies between regions and countries [ 15 ]. For example, prevalences between 97.6% and 99.2% were reported in Germany [ 16 ], 99.3% in Italy [ 17 ], 72% in Iran [ 18 , 19 ], 73.9% in Thailand [ 20 ], and 95.8% in Zambia [ 21 ], with environmental conditions, age of birds, and availability of intermediate hosts being the main determinants for the variability of parasite prevalence [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The important positive attributes of free-range (including organic) layer farming are the birds' access to an outdoor range, exposure to natural daylight (sunlight), ability to move freely, increased space to better regulate social interactions, and opportunities for expression of natural behaviours [1,2]. Free-range systems may also have some potential risks such as parasitic infections [3], increased disease exposure [4], heat stress [5], and predation [6,7]. However, welfare benefits such as reduced plumage damage and reduced footpad dermatitis can be seen in individuals that range more [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 2 species of nematodes were recovered during the study include Ascaridia galli and Heterakis gallinarum with a prevalence of (39.53 %) and (41.86 %) respectively (Raza et al, 2016). Shifaw et al, (2021) and according to a metaanalysis instead showed a high prevalence in favor of Ascaridia galli (35.9 %), followed by Heterakis gallinarum (28.5 %). Likewise, Zada et al (2015) showed a relatively low overall prevalence rate of A. galli by about 21.44 %, however A. galli was the most common and prevalent nematode in chickens in Mardan district of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Acanthocephali are exceptional in chickens (Reid & Mc Dougald, 1978). The reported prevalence of helminth species varied among species and ranged from 30 to 100 % (Shifaw et al, 2021). The parasitic species of helminths in the digestive tract are very common.…”
Section: Introductionmentioning
confidence: 99%